1972
DOI: 10.1143/jjap.11.1514
|View full text |Cite
|
Sign up to set email alerts
|

High-Resolution Video Display of X-Ray Topographs with the Divergent Laue Method

Abstract: An X-ray imaging device utilizing a high sensitivity image orthicon tube has been incorporated in the divergent Laue method of diffraction topography using a point source. An X-ray optical magnification of diffraction images has made it possible to obtain a spatial resolution better than that of the imaging device. Preliminary experiments have demonstrated that individual dislocations in silicon crystals can be displayed with a resolution of better than 25 µm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1974
1974
1977
1977

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Many authors have reported systems based on X-ray sensitive vidicons (Chikawa & Fujimoto, 1968), conventional television with phosphor screens, sometimes with image intensifiers interposed (Meieran, Landre & O'Hara, 1969;Lang & Reifsnider, 1909;Kozaki, Hashizume & Kohra, 1972) and charge sensitive diode arrays (Rozgonyi, Haszko & Statile, 1970). With conventional sources these authors reported exposure times between 0.5 s and one minute with resolutions in the range from 10/~m to 30/zm over areas of a few mm square.…”
Section: Introductionmentioning
confidence: 99%
“…Many authors have reported systems based on X-ray sensitive vidicons (Chikawa & Fujimoto, 1968), conventional television with phosphor screens, sometimes with image intensifiers interposed (Meieran, Landre & O'Hara, 1969;Lang & Reifsnider, 1909;Kozaki, Hashizume & Kohra, 1972) and charge sensitive diode arrays (Rozgonyi, Haszko & Statile, 1970). With conventional sources these authors reported exposure times between 0.5 s and one minute with resolutions in the range from 10/~m to 30/zm over areas of a few mm square.…”
Section: Introductionmentioning
confidence: 99%
“…Recent developments may be found in papers dealing with solid-state image intensifiers (60,263) and a new and potentially important device which incorporates an X-ray sensitive fiber optic faceplate (299). Several reports have appeared on instruments utilizing video display units (58,193,363). Development of phospors of improved brightness for use in image intensifier screens (218,260), as well as the development of improved intensifying screens for X-ray film, has continued (8,162,338).…”
Section: Instrumentationmentioning
confidence: 99%
“…In order to take X-ray topographs so rapidly that imperfections in crystals may be observed almost in real time, two kinds of techniques have been developed so far: one is to use the intense X-ray source and a vidicon tube with good resolution (Chikawa & Fujimoto, 1968;Chester & Koch, 1969;Rozgonyi, Haszko & Statile, 1970;Chikawa, Fujimoto & Abe, 1972;Chikawa, 1974), and the other is to use a usual source but make the detecting system sensitive with various kinds of image intensifying tubes, where electron scanning is used (Reifsnider & Green, 1968;Lang & Reifsnider, 1969;Meieran, Landre & O'Hara, 1969;Meieran, 1971;Hashizume, Kohra, Yamaguchi & Kinoshita, 1971 ;Kozaki, Hashizume & Kohra, 1972).…”
Section: Introductionmentioning
confidence: 99%